Extremely Low-Frequency Electromagnetic Fields Affect the Immune Response of Monocyte-Derived Macrophages to Pathogens - GARİP, GÜNSELİ AYŞE; AKSU, MEHMET BURAK (WILEY, 2010)
This study aimed to determine the effect of extremely low-frequency electromagnetic fields (ELF-EMF) on the physiological response of phagocytes to an infectious agent. THP-1 cells (human monocytic leukemia cell line) were cultured and 50 Hz, 1 mT EMF was applied for 4-6 h to cells induced with Staphylococcus aureus or interferon gamma/lipopolysaccharide (IF gamma/LPS). Alterations in nitric oxide (NO), inducible nitric oxide synthase (iNOS) levels, heat shock protein 70 levels (hsp70), cGMP levels, caspase-9 activation, and the growth rate of S. aureus were determined. The growth curve of exposed bacteria was lower than the control. Field application increased NO levels. The increase was more prominent for S. aureus-induced cells and appeared earlier than the increase in cells without field application. However, a slight decrease was observed in iNOS levels. Increased cGMP levels in response to field application were closely correlated with increased NO levels. ELF-EMF alone caused increased hsp70 levels in a time-dependent manner. When cells were induced with S. aureus or IF gamma/LPS, field application produced higher levels of hsp70. ELF-EMF suppressed caspase-9 activation by a small extent. These data confirm that ELF-EMF affects bacterial growth and the response of the immune system to bacterial challenges, suggesting that ELF-EMF could be exploited for beneficial uses. Bioelectromagnetics 31:603-612, 2010. (C) 2010 Wiley-Liss, Inc.
Keywords: ELF-EMF; macrophage; apoptosis; hsp70; caspase-9; NO; iNOS; cGMP; Staphylococcus aureus; HEAT-SHOCK PROTEINS; INFLAMMATORY CYTOKINE PRODUCTION; BACTERIA ESCHERICHIA-COLI; BLOOD MONONUCLEAR-CELLS; HZ MAGNETIC-FIELDS; NITRIC-OXIDE; STAPHYLOCOCCUS-AUREUS; APOPTOSIS; EXPRESSION; EXPOSURE